KARDIOCHIRURGIA DOROSŁYCHExtravalvular exoprosthetic repair of aortic root: first experience - Chernyavskiy, Alexander; Alsov, Sergey; Khvan, Dmitry; Sirota, Dmitry (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Background: Understanding the processes underlying insufficiency progression in patients with ascending aortic pathologies, as well as the structure and aortic root function, has become the basis for the development and implementation of extravalvular exoprosthetic repair of the aortic root (the Florida sleeve procedure). Material and methods : The study encompassed 10 patients with ascending aortic aneurysm with concomitant aortic insufficiency (AI) (from moderate to severe) who underwent extravalvular exoprosthetic repair of the aortic root (the Florida sleeve technique) and had a 30-day early postoperative follow-up. The mean age was 52.2 ±18.28 years. The following concomitant diseases were revealed: aortic dissection in 3 patients (DeBakey type I in 2, DeBakey type II in 1), and Marfan syndrome in 2 patients. Data were acquired preoperatively and postoperatively. Results: Postoperative echocardiographic studies demonstrate that the degree of AI decreased from the average value of 2.4 ±0.7 preoperatively down to 0.9 ±0.74 (p = 0.01) postoperatively. Mention should also be made of reverse remodeling of the left ventricle: a decrease was noted in end-diastolic volume (EDV) from 157.06 ±43.97 ml before the operation down to 127.88 ±48.91 ml (p = 0.2) after the operation. No reoperation for AI was required during the 30-day follow-up. 30-day mortality was observed in one case. Conclusions : Extravalvular exoprosthetic repair of the aortic root shows satisfactory early results. Yet, in order to analyze its early and long-term outcomes, there should be more patients involved. This could determine the advisability of the given technique when selecting surgical treatment of ascending aortic aneurysms with concomitant aortic insufficiency.